Mental Health in Pandemic Times - Alberto Palacios (Global Rheumatology, 2020)
We are filled with data, studies, and scientific information, mixed with uncertainty and fear. No prayer, barrier, or medication can stop this microscopic enemy which kills quickly and silently.